2005
DOI: 10.1177/001979390505900103
|View full text |Cite
|
Sign up to set email alerts
|

When Welfare-to-Work Programs Seem to Work Well: Explaining Why Riverside and Portland Shine So Brightly

Abstract: Of welfare-to-work programs evaluated by random assignment, two stand out as having exceptionally large estimated effects: one in Riverside, California, and the other in Portland, Oregon. The authors use data from 24 evaluations and the tools of meta-analysis to examine why. The findings indicate that the apparently superior performance of these two programs in increasing the earnings of participants is only partly attributable to program design (for example, the type of services provided, the use of sanctions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
28
0
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 15 publications
(30 citation statements)
references
References 3 publications
1
28
0
1
Order By: Relevance
“…That interpretation is confirmed by a different analysis of welfare work evaluations that had measures for service emphasis but not for emphasis on quick job entry or personalized attention. In those results, earnings impacts rose with increases in clients who were sanctioned (often for nonparticipation) and placed in job search, but fell with increases in those assigned to vocational training (Greenberg et al, 2003). The policy implications are quite similar to those suggested by Bloom, Hill, and Riccio.…”
supporting
confidence: 56%
“…That interpretation is confirmed by a different analysis of welfare work evaluations that had measures for service emphasis but not for emphasis on quick job entry or personalized attention. In those results, earnings impacts rose with increases in clients who were sanctioned (often for nonparticipation) and placed in job search, but fell with increases in those assigned to vocational training (Greenberg et al, 2003). The policy implications are quite similar to those suggested by Bloom, Hill, and Riccio.…”
supporting
confidence: 56%
“…It emphasizes immediate job search and employment because this is considered to be the best way to decrease welfare costs and reduce welfare rolls, while allowing participants to build skills that lead to better jobs (Gueron & Hamilton, 2002). Research investigating which program aspects, particularly work activities, are associated with higher earnings has suggested that engaging in unsubsidized employment resulted in increased earnings and/or likelihood of employment (Ashworth, Cebulla, Greenberg, & Walker, 2004;Greenberg, Ashworth, Cebulla, & Walker, 2005;Greenberg, Cebulla, & Bouchet, 2005;Greenberg, Michaloupoulus, & Walker, 2003). Consequently, participation in unsubsidized employment (i.e., work-first participation) is hypothesized to predict a decreased likelihood of experiencing material hardship.…”
Section: Income-and Resource-packaging Model Of Materials Hardshipmentioning
confidence: 99%
“…Sanctions are used in the TANF program to propel participants who are not compliant with rules into the labor market (Greenberg, Ashworth, et al, 2005) and to punish them for failing to engage in the required number of hours for work activities such as job readiness, job search, vocational education, paid employment, or community service (Shram, Soss, Fording, & Houser, 2009). There are at least two reasons to suspect that sanctioning might affect material hardship.…”
Section: Income-and Resource-packaging Model Of Materials Hardshipmentioning
confidence: 99%
“…Recently, scholars have begun using meta-analysis to determine which program aspects, particularly work activities, are associated with higher earnings while controlling for recipients' characteristics and the local socioeconomic environment (Ashworth et al, 2004;Greenberg et al 2005;Greenberg et al, 2003 In general, they find job search has the biggest positive effect on earnings with mixed results for basic education and vocational education training, leading researchers to discourage additional investments in education and training. They also stress the importance of considering local environment and population characteristics.…”
Section: Review Of the Literaturementioning
confidence: 99%
“…The preponderance of the evidence indicates that a work-first strategy produces the best results (Ashworth, Cebulla, Greenberg, & Walker, 2004;Greenberg, Ashworth, Cebulla, & Walker, 2005;Greenberg, Cebulla, & Bouchet, 2005;Greenberg, Michaloupoulus, & Walker, 2003). This article argues that conclusions reached under AFDC warrant additional scrutiny under TANF due to the changing policy environment.…”
mentioning
confidence: 95%